Pleiotropic effects of simvastatin are associated with mitigation of apoptotic component of cell death upon lethal myocardial reperfusion-induced injury - Rajtík, T; Čarnická, S; Szobi, A; Mesárošová, L; Máťuš, M; Švec, P; Ravingerová, T; Adameová, A (Physiological research, 2012)
Although statins exert non-lipid cardioprotective effects, their influence on cell death is not fully elucidated. For this purpose, we investigated whether simvastatin treatment (S, 10 mg/kg, 5 days) is capable of mitigating ischemia/reperfusion-induced (IR) apoptosis in the isolated rat hearts, which was examined using immunoblotting analysis. In addition, the content of signal transducer and activator of transcription 3 (STAT3) and its active form, phosphorylated STAT3 (pSTAT3-Thr(705)), was analyzed. Simvastatin induced neither variations in the plasma lipid levels nor alterations in the baseline content of analysed proteins with the exception of upregulation of cytochrome C. Furthermore, simvastatin significantly increased the baseline levels of pSTAT3 in contrast to the control group. In the IR hearts, simvastatin reduced the expression of Bax and non-cleaved caspase-3. In these hearts, phosphorylation of STAT3 did not differ in comparison to the non-treated IR group, however total STAT3 content was slightly increased. The improved recovery of left ventricular developed pressure co-existed with the increased Bcl-2/Bax ratio. In conclusion, pleiotropic action of statins may ameliorate viability of cardiomyocytes by favouring the expression of anti-apoptotic Bcl-2 and downregulating the pro-apoptotic markers; however STAT3 does not seem to be a dominant regulator of this anti-apoptotic action of simvastatin.
Keywords: Cell Death; simvastatin; krysa rodu Rattus; mužské pohlaví; Male; protein X asociovaný s bcl-2; Apoptosis; Myocardial Reperfusion Injury; reperfuzní poškození; buněčná smrt; myokard; reperfuzní poškození myokardu; Rats; bcl-2-Associated X Protein; potkani Wistar; Myocardial Infarction; Animals; Myocardium; apoptóza; Simvastatin; zvířata; Rats, Wistar; infarkt myokardu; Reperfusion Injury